Screening of Early Rice Genotypes for Red and Lateritic Areas of West Bengal - Mallick, Goutam Kumar; Kundu, C (Research in Plant Biology, 2014)
The aim of the present experiment was to screen promising early duration rice genotypes for red and lateritic areas of West Bengal. The experiment was conducted during kharif 2006, at the farm of Rice Research Station, Bankura, West Bengal, India. Among the sixty one promising rice genotypes fourteen showed significant difference in yield from the best check (Annada) of which six entries i.e. IET 20111, IET 20113, IET 20114, IET 20142 and IET 20147 exceeded flowering duration more than 90 days. So they were not considered as early rice genotypes. Rest eight rice genotypes whose 50% flowering were 90 days and less i.e. IET 20133, IET 20106, IET 20121, IET 20124, IET 20126, IET 20127, IET 20103 and IET 20128, screened as early rice genotypes suitable for red and lateritic areas of West Bengal.